ANALISIS TINGKAT PEMAHAMAN MANAJEMEN PEMASARAN TERHADAP MAHASISWA PROGRAM STUDI BISNIS DIGITAL - Maimuna, Fransiska; Roroa, Nur (Brainy: Jurnal Riset Mahasiswa, 2024)
The study aims to analyze the level of understanding of Digital Business Study Program student regarding Marketing Management. Using a qualitative method using a case study approach. The samples taken were two student of the Megarezky University Digital Business Study Program with a research time of approximately six months or one semester. An adequate understanding of this material is very important so that students are able to design and implement effective marketing strategies in today’s business environment. The results of observations show that there arev students who have a good understanding of the concepts and examples of the application of Marketing Management, and there are students who lack understanding of the concepts and examplesof the application of digital marketing management.